Marxism and Atheism. Recovering the Debate - Felip Lopez-Espinosa, Luis (Analysis. Journal of Philosophical Research, 2020)
Marxism is often identified with the outright rejection of religion. Two recent publications look at this simplification: El dispositivo Karl Marx, by Juan Manuel Aragüés, and the compilation of Marx’s texts Sobre la religión, with a preliminary study by Reyes Mate and José A. Zamora. In this article we are going to read these two works in tandem. We intend to shed new light on the problem of atheism, not just looking at the most recent contributions, but also by returning to Marx’s texts. The theoretical atheism of Marx should not be oversimplified and indeed one must see it as a consequence of his materialist conception of history, which is compatible with the practical humanism of those who share his goal of a politics of emancipation.